New 8, 17-epoxybriaranes from octocoral Briareum stechei (Kükenthal, 1908). (3rd August 2022) - Yeh, Yao-Tsung; Chen, Chun-Yu; Chen, Po-Jen; Hsieh, Yu-Hsin; Chien, Su-Ying; Liu, Chia-Jung; Wen, Zhi-Hong; Hwang, Tsong-Long; Chen, Nan-Fu; Sung, Ping-Jyun
Graphical abstract: Highlights: Two new 8, 17-epoxybriaranes, briastecholides K and L, were obtained from octocoral Briareum stechei. The absolute configuration of excavatolide E was confirmed by single-crystal X-ray diffraction analysis. Octocorals belonging to genus Briareum were proven to be rich sources of briarane-type diterpenoids. Abstract: Three 8, 17-epoxybriaranes, including a known metabolite, excavatolide M (1 ), as well as two new compounds, briastecholides K (2 ) and L (3 ), have been isolated from octocoral Briareum stechei collected off the waters of Taiwan. In this study, the absolute configuration of 1 was determined by single-crystal X-ray diffraction analysis for the first time. Moreover, the structures and stereochemistry of briaranes 2 and 3 were established based on spectroscopic analysis and comparison with those of 1 .